1975
DOI: 10.1139/z75-077
|View full text |Cite
|
Sign up to set email alerts
|

Lethal levels of pH for brook trout, Salvelinus fontinalis (Mitchill)

Abstract: Fingerling brook trout, Salvelinus fontinalis (Mitchill), were subjected to acute and chronic pH stress for maximum periods of 10 000 min in a series of dilutions of sulfuric acid or sodium hydroxide at 10 and 20C after acclimation at 15C and pH 6.8. Lethal limits of pH were estimated to be pH 3.5 and 9.8 at both temperatures. There were no observable differences in the resistance times at lethal pH stresses between test temperatures. The order of death was not significant in relation to length or weight of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…The results of the stocking experiment show that the water of Lake Laiozza is acutely toxic to brown trout, irrespective of the age of the brown trout stocked. Bearing in mind that a pH of 5.4 is considered as being not toxic to fish (Daye and Garside, 1975) and that brown trout have been found living in the chronically acid Tovdal river with a similarly ion deprived water as found in Lake Laiozza (Muniz and Lei-vestad, 1980 a), it seems unlikely that the low pH in combination with the ion deprived water of Lake Laiozza induced the observed toxicity. The symptoms of intoxication observed, the low plasma electrolyte concentrations measured, as weIl as the histopathological changes seen in the gills of the fish of the stocking experiment resembled the symptoms described for fish acutely intoxicated with high concentrations of aluminium (Dietrich, 1988, Dietrich and Schlatter, 1989, Fivelstad and Leivestad, 1984, Skogheim and Rosseland, 1986 b) so closely, that aluminium and not unspecific stress reactions resulting from the transport, seemed most likely to be the factor responsible for the lethai effects.…”
Section: Mortality and Symptomsmentioning
confidence: 99%
“…The results of the stocking experiment show that the water of Lake Laiozza is acutely toxic to brown trout, irrespective of the age of the brown trout stocked. Bearing in mind that a pH of 5.4 is considered as being not toxic to fish (Daye and Garside, 1975) and that brown trout have been found living in the chronically acid Tovdal river with a similarly ion deprived water as found in Lake Laiozza (Muniz and Lei-vestad, 1980 a), it seems unlikely that the low pH in combination with the ion deprived water of Lake Laiozza induced the observed toxicity. The symptoms of intoxication observed, the low plasma electrolyte concentrations measured, as weIl as the histopathological changes seen in the gills of the fish of the stocking experiment resembled the symptoms described for fish acutely intoxicated with high concentrations of aluminium (Dietrich, 1988, Dietrich and Schlatter, 1989, Fivelstad and Leivestad, 1984, Skogheim and Rosseland, 1986 b) so closely, that aluminium and not unspecific stress reactions resulting from the transport, seemed most likely to be the factor responsible for the lethai effects.…”
Section: Mortality and Symptomsmentioning
confidence: 99%
“…Since it has been demonstrated that mucus production can be influenced by the presence of harmful environmental factors such as stress and pollution (Christie & Battle 1963, Jakowska 1963, Eisler 1974, Daye & Garside 1975, 1976, Pickering & Macey 1977, Zuchelkowski et al 1981, we also recorded the structure and number of epidermal mucous cells. Additionally, we looked for proliferations of the gill tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases the impact of acidification cannot be ascribed to pH decrease alone. Brooktrout, Salvelinus fontinalis (Mitchell), for instance, seem to suffer mainly from toxic aluminium concentrations mobilized by increasing acidification, as they are able to tolerate substantial additions of sulphuric acid (Daye and Garside, 1975). It is also known that heavy metals are more toxic to algae at low pH (Voigt, 1979).…”
Section: Introductionmentioning
confidence: 99%